Poor diagnostic values of stool analysis and steatocrit test in detecting exocrine pancreatic insufficiency (Medical Journal of Indonesia, 2019)
BACKGROUND Exocrine pancreatic insufficiency (EPI) is one of the most challenging cases to be diagnosed accurately in Indonesia because of the unavailability of the fecal elastase-1 (FE-1) test, which is the primary indirect diagnostic tool till date. Stool analysis and steatocrit test are feasible alternatives as they can detect nutrient malabsorption, a consistent feature in EPI. Despite the common practice of using both tests, no study has ever been conducted in Indonesia to evaluate their accuracy. METHODS This cross-sectional diagnostic study was conducted in 182 children aged 6-60 months. Study subjects were divided into children with persistent diarrhea (PD), those with malnutrition, and healthy children. Children with PD and malnutrition were selected on the basis of clinical criteria and the WHO z-score. FE-1 test was used as the gold standard to detect EPI. Primary endpoints of this study were sensitivity and specificity of the stool analysis and the steatocrit test. The accuracy of both tests, represented by area under the curve (AUC) values, was also evaluated individually and in combination. RESULTS Each component of stool analysis and steatocrit test in each subgroup of patients generally had higher specificity than sensitivity. The specificity of both tests among healthy and malnourished children was good (≥70%), but among children with PD, the specificity of some components was <70%. The individual and combined AUC values of both tests in each subgroup of subjects were poor (<0.7). CONCLUSIONS Stool analysis and steatocrit test cannot be used as alternative methods for FE-1 to detect EPI.